2020
DOI: 10.1038/s41598-020-75675-5
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 binding protein (IL-18BP) as a novel radiation countermeasure after radiation exposure in mice

Abstract: Recent studies suggested that radiation exposure causes local and systemic inflammatory responses and induces cell and tissue damage. We have reported that IL-18 plays an important role in radiation-induced injury. Here, we demonstrate that IL-18 binding protein (IL-18BP), a natural antagonist of IL-18, was significantly increased (1.7–63 fold) in mouse serum on day 1 after 0.5–10 Gy TBI. However, this high level of IL-18BP was not sufficient to neutralize the active IL-18 in irradiated mice, resulting in a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…IL-18 binding protein (IL-18BP) is a natural antagonist of IL-18, belonging to the immunoglobulin like receptor type but is not cleaved on cell surface ( 221 ). It is a naturally occurring 18 binding agent was first identified in 1999.…”
Section: Monoclonal Antibodies and Drugs Targeting Il-18mentioning
confidence: 99%
“…IL-18 binding protein (IL-18BP) is a natural antagonist of IL-18, belonging to the immunoglobulin like receptor type but is not cleaved on cell surface ( 221 ). It is a naturally occurring 18 binding agent was first identified in 1999.…”
Section: Monoclonal Antibodies and Drugs Targeting Il-18mentioning
confidence: 99%
“…Circulating IL-18 has been shown to be a biomarker of exposure to TBI in three animal models, namely mice, minipigs, and non-human primates. 71 , 72 Administration of human rIL-17B has been shown to promote neutrophil migration in healthy mice. 73 Moreover, IL-17 family members induce inflammatory cytokines not only through activated T cells but also through activated monocytes/macrophages, which are the primary cells in the bone marrow that are damaged by exposure to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Li et al (2020) used recombinant human IL-18 (rhIL-18BP) to decrease soluble IL-18 in irradiated experimental mouse. The administration of IL-18BP was found to inhibit the down-stream activities of IL-18, and the treated mouse showed low levels of IFN-g, reactive oxygen species (ROS) as well as attenuated a stress responsive factor named growth differentiation factor-15 (GDF-15) (132). The study was encouraging as it showed that IL-18 played a paramount role in radiation-induced tissue damage and treatment with IL-18BP likely mitigates tissue injury/ damage induced by radiation.…”
Section: C) Targeting Il-18mentioning
confidence: 99%